2022
DOI: 10.3389/ftox.2022.852856
|View full text |Cite
|
Sign up to set email alerts
|

Application of Defined Approaches for Skin Sensitization to Agrochemical Products

Abstract: Skin sensitization testing is a regulatory requirement for safety evaluations of pesticides in multiple countries. Globally harmonized test guidelines that include in chemico and in vitro methods reduce animal use, but no single assay is recommended as a complete replacement for animal tests. Defined approaches (DAs) that integrate data from multiple non-animal methods are accepted; however, the methods that comprise them have been evaluated using monoconstituent substances rather than mixtures or formulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…For this reason, human data were available in the literature only for a limited number of the substances in this study (n=5). The limited availability of human reference data is far from unique to the present study, and a recent example includes the assessment of agrochemical formulations (Strickland et al, 2022), for which the authors reported all performance metrics of evaluated NAMs exclusively versus available animal data. In addition, animal data from the assay or the GPMT were available for a total of eight and three compounds, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, human data were available in the literature only for a limited number of the substances in this study (n=5). The limited availability of human reference data is far from unique to the present study, and a recent example includes the assessment of agrochemical formulations (Strickland et al, 2022), for which the authors reported all performance metrics of evaluated NAMs exclusively versus available animal data. In addition, animal data from the assay or the GPMT were available for a total of eight and three compounds, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The first three key events have in chemico and in vitro assays outlined in OECD 442A-E. These assays are routinely utilized for the assessment of agrochemical active ingredients , and formulations , and can be adapted into non-GLP studies for early stage screening. Finally, the data interpretation of in chemico , in vitro , and in silico assessments of sensitization potential are outlined in OECD 497, which includes interpretation for a “2 out of 3” and “integrated testing strategy” (ITS) approaches for data interpretation.…”
Section: Acute Toxicitymentioning
confidence: 99%
“…In addition, Strickland et al extended the applicability of DA to 27 mixtures of agrochemicals [18], considering only active ingredients. In their study, the animal assay data without human evidence were compared with the adjusted DA approach, and individual methods include the DPRA assay, KeratinoSens assay, h-CLAT assay, and QSAR Toolbox.…”
Section: Datasetmentioning
confidence: 99%
“…The commercial software Derek and the corresponding ITSv1 approach were not included in the comparison due to the tool being commercial. To predict the mixture, Strickland et al [18] followed OECD guidelines [4][5][6] with minor modifications regarding conducting the in chemico and in vitro experiments. In addition, they followed the GHS guidance for in silico results, which classify a sensitizer mixture by at least one sensitizer ingredient whose concentration is more than 0.1%.…”
Section: Datasetmentioning
confidence: 99%
See 1 more Smart Citation